2016 46th Annual IEEE/IFIP International Conference on Dependable Systems and Networks (DSN) 2016
DOI: 10.1109/dsn.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

OSIRIS: Efficient and Consistent Recovery of Compartmentalized Operating Systems

Abstract: Much research has gone into making operating systems more amenable to recovery and more resilient to crashes. Traditional solutions rely on partitioning the operating system (OS) to contain the effects of crashes within compartments and facilitate modular recovery. However, state dependencies among the compartments hinder recovery that is globally consistent. Such recovery typically requires expensive runtime dependency tracking which results in high performance overhead, high complexity and a large Reliable C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We found that, compared to other platforms, QEMU is marking more instructions as valid that are also considered as valid by the disassem-bler. This concerns optional instruction set extensions that are not implemented by other platforms 1 . Single unimplemented instructions with large immediate fields cause many thousands of values to be marked as disassembler faults, this causes the large difference of disassembler faults between QEMU and the other systems and also the large difference in undocumented instructions between the systems.…”
Section: B Armv8 A64 Scan Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that, compared to other platforms, QEMU is marking more instructions as valid that are also considered as valid by the disassem-bler. This concerns optional instruction set extensions that are not implemented by other platforms 1 . Single unimplemented instructions with large immediate fields cause many thousands of values to be marked as disassembler faults, this causes the large difference of disassembler faults between QEMU and the other systems and also the large difference in undocumented instructions between the systems.…”
Section: B Armv8 A64 Scan Resultsmentioning
confidence: 99%
“…Correct and secure operation of computer systems depends on both software and hardware. Many efforts to improve the operation of computer systems focus mainly on the software stack, such as for instance development of operating system crash recovery methods [1] and hardening of the software system's security [2]. Hardware, and in particular processors, are treated as trusted black boxes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the complexity of these recovery kernels is comparable to that of a small hypervisor. For example, OSIRIS [57] directs OS recovery to a 29 KLOC reliable computing base (RCB) [60], roughly twice the size of modern microkernels [12], [22], [35], [61]. Again, this makes the likelihood of residual faults or vulnerabilities non-negligible.…”
Section: Related Workmentioning
confidence: 99%